PI3Kinase-p110δ Overexpression Impairs Dendritic Morphogenesis and Increases Dendritic Spine Density - Hood, Veronica L.; Paterson, Clare; Law, Amanda J. (Frontiers in Molecular Neuroscience, 2020)
Activity and expression of the phosphoinositide 3-kinase (PI3K) catalytic isoform, PIK3CD/p110, is increased in schizophrenia, autism, and intellectual delay and pro-cognitive preclinical efficacy of p110-inhibition has been demonstrated in pharmacological, genetic, and developmental rodent models of psychiatric disorders. Although PI3K signaling has been implicated in the development and function of neurons and glia; isoform-specific roles of the individual PI3Ks are less clear and the biological effects of increased p110 on neuronal development are unknown. Since the pathobiological direction of p110 changes in neurodevelopmental disorders is increased expression and activity, we hypothesized that overexpression of p110 would impact measures of neuronal development and maturation relevant to connectivity and synaptic transmission. p110 overexpression in primary rat hippocampal cultures significantly reduced dendritic morphogenesis and arborization and increased immature and mature dendritic spine densities, without impacting cell viability, soma size, or axon length. Together, our novel findings demonstrate the importance of homeostatic regulation of the p110 isoform for normative neuronal development and highlight a potential pathophysiological mechanism of association to disorders of neurodevelopment.